The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1111/jabr.12096
|View full text |Cite
|
Sign up to set email alerts
|

Pain catastrophizing may moderate the association between pain and secondary hyperalgesia

Abstract: Catastrophizing, a persistent negative mental set characterized by helplessness, rumination, and magnification of pain sensations, has a potent effect on pain report and clinical outcomes. Previous studies have documented an association between cognitive factors and central sensitization.The current analysis sought to test the potential modulating effect of pain catastrophizing on the association between capsaicin pain and the region of secondary hyperalgesia. Thirty-eight healthy individuals (50% women, mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…43 In an experimental pain setting, Pressman and co-workers found that in healthy individuals, relatively low levels of catastrophising (PCS 10.6) moderated the association between pain and such secondary hyperalgesia. 44 Therefore, in samples with similar subclinical levels of pain catastrophising such as ours, mild catastrophic thinking may be an early predictor of pain chronification, a notion that warrants further research.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…43 In an experimental pain setting, Pressman and co-workers found that in healthy individuals, relatively low levels of catastrophising (PCS 10.6) moderated the association between pain and such secondary hyperalgesia. 44 Therefore, in samples with similar subclinical levels of pain catastrophising such as ours, mild catastrophic thinking may be an early predictor of pain chronification, a notion that warrants further research.…”
Section: Discussionmentioning
confidence: 67%
“…The pain attention behaviour embedded in catastrophic thinking could, however, be a significant mediator in the transition from acute to chronic pain condition; a hyperalgesic state often associated with widespread pain 43 . In an experimental pain setting, Pressman and co‐workers found that in healthy individuals, relatively low levels of catastrophising (PCS 10.6) moderated the association between pain and such secondary hyperalgesia 44 …”
Section: Discussionmentioning
confidence: 99%